Inhibition of biofilm formation by a lipopolysaccharide-associated glycosyltransferase in the bacterial symbiont Vibrio fischeri - Provencher, Edward A. P.; Ehrig, Molly R.; Cecere, Andrew G.; Cousins, Shyan C.; Maybin, Michael A.; Meredith, Timothy C.; Miyashiro, Tim I. (Frontiers in Bacteriology, 2023)
Many animals form symbioses with environmental bacteria that provide express traits biological functions beneficial to their hosts. The mechanisms that affect the acquisition of bacterial symbionts remain poorly understood but are important to identify to develop new ways to improve animal health. Vibrio fischeri is a Gram-negative bacterium that forms a mutualistic symbiosis with the Hawaiian bobtail squid Euprymna scolopes. From within a light organ, these V. fischeri populations engage in quorum sensing to produce bioluminescence for the host to eliminate its shadow. In our attempts to investigate how quorum sensing contributes to the evolution of V. fischeri, we unexpectedly isolated a strain that produced large structures resembling biofilms along glass surfaces that readily stain with crystal violet. Biofilm formation by this strain is independent of sypG, which encodes the primary activator of the symbiotic polysaccharide (syp) locus, suggesting a novel biofilm pathway. Squid colonization assays revealed that the isolate exhibited a colonization defect, which suggests that its biofilm phenotype inhibits establishment of symbiosis establishment. Whole-genome sequencing and subsequent culture assays suggest that this biofilm phenotype is due to a single point mutation that confers an I125F substitution in the putative glycosyltransferase VF_0133. Expression of the wild-type copy of VF_0133 in trans eliminates the biofilm-like phenotypes in culture and restores the ability of the strain to establish symbiosis. Investigation of lipopolysaccharide (LPS) structure by silver stain suggests significant modifications to the oligosaccharide core and Oantigen in this strain. Taken together, these findings add knowledge to the role of LPS in V. fischeri physiology and light organ colonization, which provides important insight into how bacterial symbionts are acquired from the environment.